(untitled) (Fiep Bulletin - online, 2014)
Talking about Gymnastics in different contexts makes us, at a first moment, thinking about which Gymnastics has been considered and which context we´re talking bout. Among so many terms and definitions used in the current society, we sometimes reduce its meaning to the activities practiced in gymnasiums or to activities practiced in sports. In this article we discuss Gymnastics in its whole meaning presenting different Gymnastics types and objectives that were acquired in the capitalist society, and also questioning how Gymnastics has been managed in the education and non-education context.